ANALISIS KESEIMBANGAN EKSPOR DAN IMPOR CRUDE PALM OIL (CPO) INDONESIA - Syahril Syahril; Affandi Affandi; Okta Rabiana Risma; Rollis Juliansyah (JURNAL EKOMBIS, 2019)
This research aims study is to explain the area of oil palm, the productivity of oil palm, CPO export offers for the year, CPO import demand and the balance of Indonesia CPO export and import. we use time series data for 1981-2014 years and econometrics models in the form of simultaneous equations with 2SLS method. The focus of the study is the balance of Indonesia's CPO export and import for the period 1981-2014 years. Statistical analysis of multiple linear regression using the Shazam 10. F Test Results show that the current domestic CPO prices, current domestic rubber prices, the area of oil palm land in the previous year had a significant effect on land area. Current CPO export prices, current domestic CPO prices, and previous year's oil palm productivity have a significant effect on CPO productivity and the current fertilizer prices have no significant effect. Current CPO export prices, current CPO production and previous year's CPO exports, the current rupiah exchange rate against the dollar today has a significant effect on CPO export offers while the current rupiah against the dollar has no significant effect on export offers. Current CPO import prices, current GDP have a significant effect on CPO import demand while the previous year's import demand had no significant effect on import demand. The CPO export offer of the previous year had a significant effect on the balance of Indonesia's CPO export prices while the rupiah exchange rate against the current dollar, current CPO production, CPO export of the previous year, current year's GDP and import of the previous year had no significant effect on Indonesia's CPO export price balance. Keywords: Land Area, Domestic CPO Production, CPO Productivity, CPO Exports, CPO Imports, Domestic CPO Prices, CPO Export Prices, CPO Import Prices, Rubber Prices, Exchange Rates, GDP and Fertilizer Prices.